Survival and Habitat Use of Wild Pheasant Broods on Farmland in Lower Austria - Thomas H. Bliss; Brandon C. Anderson; Roger A.H. Draycott; John P. Carroll (National Quail Symposium Proceedings, 2017)
Wild pheasants (Phasianus colchicus) have declined throughoutmuch of their European distribution. The influence of habitat composition on survival and habitat use of wild pheasant broods is not well understood, but is important for population management. We studied the brood-rearing ecology of pheasants using radio-tagged hens on a 2,400 ha farming estate in Lower Austria during 2001-2003. Brood survival , ≥ 1 chick surviving to 3 weeks, (n = 36) were: 74.4% (15.6 SE), 91.9% (7.8 SE), and 65.7% (13.8 SE), during 2001-2003, respectively. Complete brood loss (n = 7) occurred between 2 -17 days after hatching with predation (n = 5) accounting for 71.4% of losses. Survival of broods was influenced by composition of habitats within fixed kernel home ranges. Proportion of planted game crop, mixture of legumes and grasses, within the home range had a positive effect on survival, whereas age and condition of females did not influence brood survival. To improve brood survival rates of pheasants in agricultural landscapes farmers and game managers should consider planting specialist brood rearing mixtures in areas close to nesting habitat.
Keywords: Austria; brood survival; compositional analysis; habitat; home range; Phasianus colchicus; wild pheasant